(untitled) (Research, Society and Development, 2021)
This work compiles the scientific productions present in the literature, which bases the proposal of a methodology for technical dimensioning of tubular biodigesters. The proposed methodology presents a simplified and organized calculation routine that allows the user, based on two basic information (quantity and class that the animal belongs to), to obtain as results the geometric parameters of the biodigester pit and auxiliary boxes. In general, the design of the biodigester is based on defined geometric parameters that consider the volume of residues generated daily and the time that these residues must be retained for biodigestion to occur. This volume is estimated based on the energy needs of each property (biogas production), the number of animals present and the area available for application of the biofertilizer. The dimensions of the fossa estimated in the methodology were the volume (cubic meters), the width (meters), the length (meters) and the useful height (meters). The design methodology was presented synthesized in a flowchart. Having as primary data the type and number of animals, the procedure for the calculation requires a regional adaptation of each producer, considering the available literature, with data on hydraulic retention time and estimated amount of waste per day.